Growth, yield and postharvest quality of wax apple as affected by naphthalene acetic acid application - Mohammad Moneruzzaman, Khandaker; A.B.M. Sharif, Hossain; Normaniza, Osman (2015)
Results of this study represent the first report of the effect of Naphthalene Acetic Acid (NAA) on the pre and post harvest quality of wax apple fruit. The wax apple trees were spray treated with 0, 5, 10 and 20 mg L-1 NAA under field conditions during 2008 to 2011. The experiments were carried out in Completely Randomized Design (CRD) with six replications. Leaf chlorophyll content, chlorophyll fluorescence, photosynthetic yield, net photosynthetic rate, drymatter content of leaves and total soluble solids and K+ content of wax apple fruits were significantly increased after treatments with 10 mg L-1. Polygalacturonase activity significantly decreased with NAA treatments. The application of 5 mg L-1 NAA increased 27% more bud and reduced 42% less fruit drop compared to the control. In addition, higher protein and phosphate synthase activity of leaves, fruit set, fruit growth, larger fruit size and yield were recorded in NAA treated plants. In storage, treated fruits exhibited higher TSS and firmness and less weight loss, browning, titratable acidity, respiration and ethylene production than the control. It is concluded that spraying with 5 and 10 mg L-1 NAA once a week under field conditions produced better fruit growth and yield of the wax apple and maintained better fruit quality in postharvest storage.